The law of organized religions between establishment and secularism - Rivers, Julian (Oxford : Oxford University Press, 2010)
This title offers a systematic account of the law that applies to religious bodies. It sets the modern law in its historical context, and examines the major controversies relating to the legal control of religious practice, including faith schools faith-based welfare provision, and the human rights law protecting religious freedom.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Religious institutions -- Law and legislation -- England; Religious institutions -- Law and legislation -- Wales; Christianity and law